Simultaneous Determination of Lamotrigine, Oxcarbazepine, Lacosamide, and Topiramate in Rat Plasma by Ultra-Performance Liquid Chromatography-Tandem Mass Spectrometry - Erjie Qiu; Lu Yu; Qishun Liang; Congcong Wen (International Journal of Analytical Chemistry)
This study established an ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method to study the pharmacokinetics of four antiepileptic drugs, lamotrigine, oxcarbazepine, lacosamide, and topiramate, in rats after oral administration. The gradient elution was performed on a UPLC HSS T3 (2.1 mm × 100 mm, 1.8 μm) column with acetonitrile-0.1% formic acid as the mobile phase at a flow rate of 0.4 mL/min. Protein precipitation by acetonitrile was adopted for plasma sample pretreatment. Electrospray- (ESI-) positive/negative ion switching and multiple reaction monitoring (MRM) modes were adopted for ion quantitative determination of antiepileptic drugs. UPLC-MS/MS detection and Drug and Statistics (DAS) software fitting were performed to blood samples collected from rats after oral administration of lamotrigine, oxcarbazepine, lacosamide, and topiramate (5 mg/kg). All drugs examined showed linearity within 5–5000 ng/ml (R2 > 0.9987), the intraday accuracy was within 92%–108%, and the interday accuracy was within 93%–109%. The relative standard deviations (RSD) of intraday and interday were less than 15%. The matrix effect was within 91%–105%, and the recovery was better than 88%. The established UPLC-MS/MS method was successfully applied to the pharmacokinetic study of lamotrigine, oxcarbazepine, lacosamide, and topiramate in rats.